Determinants of CEO bonus compensation - Chwei Cheng Wang; Chih Chi Fang; Yung-I Lou; Zhaohui Xu (Financial Internet Quarterly, 2021)
The primary purpose of this study is to explore the determinants of CEO bonus compensation: to examine CEO bonuses and to explore whether or not the independent variables are associated with CEO bonus compensation. For the purposes of this study, a sample of 2,448 CEO bonus compensations across 1,622 firms from 1997 to 2002 was used to test several hypotheses. The dependent variable in this model is the CEO bonus compensation. Bonus is the dollar value of the bonus (cash and non-cash) earned by the named executive officer during the fiscal year. Corporate diversification was divided into two categories; international diversification and industry diversification. Firm performance is measured by both Market-based, Performance (RET) and Accounting-based, Performance (ACE). The results show that the higher the degree of international diversification, and the higher accounting earnings performance, the more CEOs receive in bonuses. In addition, this study found that international diversification is associated with a greater use of bonuses and with a greater reliance on accounting-based, rather than marketbased measures of firm performance. The results also demonstrated that CEOs in firms with more investment opportunities will receive higher bonuses than CEOs in firms with fewer investment opportunities and CEOs in larger firms will receive higher bonuses than CEOs in smaller firms.
Keywords: M4; M12; 330; CEO bonus compensation; corporate diversification; international diversification; industrial diversification; investment opportunity; stock ownership